Caesar's last breath : decoding the secrets of the air around us - Kean, Sam (Little, Brown and Company, 2017)
A round-the-globe journey through the periodic table explains how the air people breathe reflects the world's history, tracing the origins and ingredients of the atmosphere to explain air's role in reshaping continents, steering human progress, and powering revolutions.